Assembling, Computational and Experimental Insight of Self-assembled Carbo Benzyl oxy-L-Alanyl-L-Valine Benzyl Ester: A Novel Free Radical Scavenger and Photo Therapeutic Nano Molecular System - Sivanathan, M.; Naveenkumar, R.; Karthikeyan, B. (Current Indian Science, 2024)
IntroductionThis work investigates the synthesis of self-assembled novel carbo benzyl oxy - L - alanyl - L - valine benzyl ester (CBAVBE).MethodsThorough studies of the morphology, optical, and structural investigations by UV-Visible, UV-DRS, FT-IR, FT-Raman, HR-TEM, and FE-SEM are used to characterize the self-assembled CBAVBE and computational studies also investigated. The anti-oxidant capability of carbo benzyl oxy - L - alanyl - L - valine benzyl ester is evaluated after self-assembly.ResultsFT-IR and Raman analysis have proven that specific chemical bonds exist in the self-assembled CBAVBE. FE-SEM analysis clearly confirms that the CBAVBE is fibrous in nature, and the collected images clearly show the CBA assembly VBE to be well aggregated. The docking analysis suggests that the CBAVBE molecule has inhibitory action against brain and lung cancer protein but biological study is needed to validate the results. An antioxidant study reveals the potential of the selected CBAVE as a notable biomarker.ConclusionA new class of self-assembled peptide nano self-assemblies have been marked as a discovery that could be used to treat a variety of diseases.
Keywords: Free radical scavenging